Co decyduje o jakości naszych rozmów z innymi? Wybrane podmiotowe wyznaczniki stylu konwersacyjnego i kompetencji komunikacyjnej - Lewandowska, Bianka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article discusses two theoretical notions, which represent individual differences in range of interpersonal communication: conversational style and level of communicative competence. It compares some manners of defining above-mentioned. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 259-275